Case Report: Trametinib in the treatment of patients with metastatic lung adenocarcinoma harboring NF1 mutation: a case series and literature review - Kim, Floryane; Borgeaud, Maxime; De Vito, Claudio; Tsantoulis, Petros; Addeo, Alfredo (Frontiers in Oncology, 2025)
BackgroundThe neurofibromin 1 (NF1) protein regulates the downstream RAS/RAF/MEK/ERK pathway and functions as a tumor suppressor. Somatic pathogenic mutations in NF1 are found in approximately 4.7%–10% of NSCLC, with a higher frequency in lung adenocarcinomas, reaching up to 15% in certain cohorts. Trametinib, a MEK inhibitor, has demonstrated activity in tumors with NF1 alteration in preclinical models, and clinical activity in low-grade glioma and plexiform neurofibromas in neurofibromatosis type 1. Trametinib had only limited clinical efficacy in other tumor types with NF1 mutations in the NCI-Match trial. However, the sole NSCLC patient that was evaluable for response in the NCI-Match trial benefited from a deep partial response. More data for the activity of MEK inhibitors in NF1 altered NSCLC are needed.Cases presentationWe report here a series of four NSCLC patients with NF1 pathogenic mutations treated with trametinib. All patients underwent extensive molecular testing with next-generation sequencing (custom 462-gene panel) and copy number variation analysis and were deemed to have potential NF1-loss-driven tumors after a case discussion in a multidisciplinary molecular tumor board. Two patients exhibited homozygous NF1 LOF alterations, whereas two patients had heterozygous loss-of-function alterations. All patients were treated with oral trametinib 2 mg once daily, after failure of standard therapies. Trametinib was administered for a maximum duration of 9 weeks. The best response observed was a stable disease in one patient. All patients died within 3 months of treatment initiation. No side effects warranted treatment cessation.ConclusionIn this small case series, NSCLC patients with NF1 alterations did not derive clinical benefit from trametinib. While these data do not support trametinib as a treatment option for NF1-mutated NSCLC, larger studies are required to draw firm conclusions.